Effects of the in-medium NN cross sections in heavy ion collisions on particle production - Prassa, V.; Gaitanos, T.; Lalazissis, G.; Di Toro, M.; Wolter, H. H. (HNPS Advances in Nuclear Physics, 2019)
The density dependence of the in-medium nucleon-nucleon (NN) cross sections is investigated in terms of particle production in heavy ion collisions (HIC). It is found, in particular, that the in-medium modifications of the inelastic NN cross sections considerably affect the pion yields and improve the comparison with experimental information. Such studies are important in determining the still unknown behavior of the nuclear equation of state (EoS) at supra-normal densities in HIC.